The Impact of Digital Finance on Industrial Structure Upgrading—A Factor of Production Perspective - Sun, Wenwen (Journal of Global Economy, Business and Finance, 2025)
High-quality development is central to building a modern socialist country, with industrial structure upgrading as a key pathway. In the era of globalization, strategic industrial planning and the transformation of traditional industries are vital for establishing the “dual circulation” development pattern, enhancing domestic market resilience and international competitiveness. This paper investigates the impact mechanisms of digital finance on industrial structure upgrading from a factor of production perspective. Using panel data from 290 Chinese prefecture-level cities (2011–2024), a Panel Vector Autoregression (PVAR) model is constructed to analyze the dynamic relationships among digital finance, industrial upgrading, and factor endowments. The findings reveal a time-lag effect: digital finance’s impact is limited in the short term but becomes significantly positive over the long term, demonstrating its sustained potential to drive industrial transformation.